2021
DOI: 10.1021/acs.jpcc.1c03549
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Electron-Beam Manipulation of Single-Dopant Atoms in Silicon

Abstract: The precise positioning of dopant atoms within bulk crystal lattices could enable novel applications in areas including solid-state sensing and quantum computation. Established scanning probe techniques are capable tools for the manipulation of surface atoms, but at a disadvantage due to their need to bring a physical tip into contact with the sample. This has prompted interest in electron-beam techniques, followed by the first proof-of-principle experiment of bismuth dopant manipulation in crystalline silicon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…This leads to the removal of either one of the lattice atoms or the impurity atom after a stochastically determined number of steps that depends on the electron energy. 121 However, a similar manipulation process has also been demonstrated for Bi 137 and Sb 117 dopants in bulk silicon, which may prove more robust due to the 3D lattice. The contrast of lighter dopants would present a major challenge, but it also appears that the same mechanism does not work for P and As 117 —highlighting the value of simulations in guiding experiments.…”
Section: Manipulating Single Atomsmentioning
confidence: 82%
See 3 more Smart Citations
“…This leads to the removal of either one of the lattice atoms or the impurity atom after a stochastically determined number of steps that depends on the electron energy. 121 However, a similar manipulation process has also been demonstrated for Bi 137 and Sb 117 dopants in bulk silicon, which may prove more robust due to the 3D lattice. The contrast of lighter dopants would present a major challenge, but it also appears that the same mechanism does not work for P and As 117 —highlighting the value of simulations in guiding experiments.…”
Section: Manipulating Single Atomsmentioning
confidence: 82%
“…Here, the host lattice atom originally neighboring the impurity ends up as its second-nearest neighbor, with another lattice atom taking over the position originally occupied by the impurity atom. We therefore named this process "indirect exchange", where, crucially, vacancies do not need to be created 117 .…”
Section: Manipulation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Narrowing the bandgap of catalysts via chemical doping is an effective approach to enhance their photocatalytic activity and hence to better utilize the solar energy. , Dopants can generally nurture new physical and chemical properties for the host 2D materials, for instance, by introducing new energy states or by lowering the conduction band minimum (CBM) that results in bandgap reduction. Chemical doping can also tune the reactivity of catalyst surfaces to improve their HER performance. ,,, Quantum chemical calculations have predicted that different atomic configurations of dopants exhibit strong effects on the electronic properties and reactivity of 2D materials . Precise positioning of dopant atoms on material surfaces can be manipulated experimentally using, for instance, scanning probe microscopy and scanning transmission electron microscopy. Many theoretical and experimental studies have been carried out aiming to understand the effects of chalcogenide doping (e.g., S and Te) on the bandgap of 2D GaSe and its UV/visible absorption properties. Experimental studies showed that the emission band of bulk GaSe at 625 nm (or 1.98 eV) was red-shifted to 688 nm (or 1.80 eV) for GaSe 0.5 Te 0.5 nanoflakes .…”
Section: Introductionmentioning
confidence: 99%